Choroidal hemodynamics in central serous chorioretinopathy after half-dose photodynamic therapy and the effects of smoking - Etsuyo Horiguchi; Jun Takeuchi; Ryo Tomita; Keiko Asai; Yuyako Nakano; Hikaru Ota; Yosuke Taki; Yasuki Ito; Hiroko Terasaki; Koji M. Nishiguchi; Keiko Kataoka (Scientific Reports, 2022)
Abstract This retrospective study aimed to evaluate choroidal hemodynamics after half-dose photodynamic therapy (PDT) for central serous chorioretinopathy (CSC) and the effects of smoking using laser speckle flowgraphy. This study included 29 eyes of 29 patients treated with half-dose PDT for CSC, who were followed-up for at least 6 months. The mean blur rate (MBR) in the PDT irradiation area (whole area), the pachyvessel (PV) area, non-PV (NPV) area, and filling delay (FD) area were assessed at baseline and 1, 3, and 6 months post-PDT, respectively. The MBR was also assessed by smoking status. The MBR significantly decreased from baseline in the whole, PV, NPV, and FD areas at all time points (P < 0.001). Of the 29 patients, 6 were never smokers, 13 were past smokers, and 10 were current smokers. At baseline, no significant difference was found in the MBR in the whole, PV, NPV, and FD areas among never, past, and current smokers. The MBR changes showed a significantly smaller decrease in current smokers than in never smokers in the whole (P = 0.021), PV (P = 0.009), and NPV (P = 0.034) areas, but not in the FD area (P = 0.172). Half-dose PDT for CSC reduced choroidal blood flow in the PDT-irradiated area, which was blunted by current smoking status.